Hukuman Mati, Alkitab dan HAM - Endang Pasaribu (JURNAL KADESI, 2021)
This study aims to reveal,produce data and facts whether the death penalty is something that is in line with human rights and the Bible as a Christian foundation. The benefits of this research theoretically provide an understanding to the wider community about the death penalty and human rights, increase and equip society to have This research uses descriptive qualitative methods, this method is used for social and humanities research and can also be used in theological studies. The results of this study indicate that the death penalty in Indonesia is a standard and legal matters in the Criminal Code, even though human rights are not in line and in agreement with its implementation, the death penalty will still be implemented if the Criminal Code does not undergo a revision in the chapter that contains the death penalty. The implementation of this research is to teach every person or Christian to be the authority to accept and be responsible for receiving the death penalty, because it is impossible for the death penalty to be given to a person who has not committed a crime.